Implementação e uso de tecnologias para automação do atendimento nos supermercados de Fortaleza: um olhar a partir da posição dos agentes envolvidos - Silva, Marcus Ângelo Alves da Costa (2024)
This research seeks to answer what factors have caused self-service technologies to be implemented in Fortaleza supermarkets in the form they have. To this end, a case study with an explanatory purpose and a qualitative approach was carried out, especially guided by semi-structured interviews, in order to note the potentialization of gains, the control of work and the modification of consumption (hypotheses initially raised). It shows that in Fortaleza there is low take-up of these machines by supermarkets (less than 15%), even though their effectiveness is recognized by all the agents involved: consumers, manufacturers, managers of supermarkets that have adopted self-checkout and those that have not. It can be concluded, therefore, that the implementation of self-service in Fortaleza has a particular impact on the time taken to provide the service, i.e.: consumers spend less time in the supermarket; supermarket workers' working time is used for other activities; and the time taken to collect revenue from the sale of goods becomes faster. Despite this, the implementation is not more significant due to a characteristic of Fortaleza that is also, given the proportions, characteristic of Brazil and the Global South: abundant and cheap labor.